Human BIN1 isoforms grow, maintain, and regenerate excitation–contraction couplons in adult rat and human stem cell-derived cardiomyocytes. Issue 6 (21st June 2021) - Guo, Jia; Tian, Qinghai; Barth, Monika; Xian, Wenying; Ruppenthal, Sandra; Schaefers, Hans-Joachim; Chen, Zhifen; Moretti, Alessandra; Laugwitz, Karl-Ludwig; Lipp, Peter
Abstract: Aims: In ventricular myocytes, transverse-tubules (T-tubules) are instrumental for excitation–contraction (EC)coupling and their disarray is a hallmark of cardiac diseases. BIN1 is a key contributor to their biogenesis. Our study set out to investigate the role of human BIN1 splice variants in the maintenance and regeneration of EC-coupling in rat adult ventricular myocytes and human-induced pluripotent stem cell-derived cardiac myocytes (hiPS-CMs). Methods and results: In heart samples from healthy human donors expression patterns of five BIN1 splice variants were identified. Following viral transduction of human BIN1 splice variants in cellular models of T-tubular disarray, we employed high-speed confocal calcium imaging and CaCLEAN analysis to identify functional EC-coupling sites (couplons) and T-tubular architecture. Adult rat ventricular myocytes were used to investigate the regeneration after loss and maintenance of EC-coupling while we studied the enhancement of EC-coupling in hiPS-CMs. All five human BIN1 splice variants induced de-novo generation of T-tubules in both cell types. Isoforms with the phosphoinositide-binding motif (PI) were most potent in maintenance and regeneration of T-tubules and functional EC-coupling in adult rat myocytes. In hiPSC-CMs, BIN1 variants with PI-motif-induced de novo generation of T-tubules, functional couplons and enhanced calcium handling. Conclusion: BIN1 is essential for the maintenance, regeneration, and de novo generation of functional T-tubules. Isoforms with PI-motifs appeared as particulalrly potent. These T-tubules trigger the development of functional couplons resulting in enhanced calcium handling. Graphical Abstract: